Factor2x2x6

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ) From the second term, you have a "–b" left over: 2(x – y) – b(x – y) = (x – y)(2 – b) Factor x(x – 2) + 3(2 – x). = x(x – 2) + 3(2 – x) =x(x ­ 2) + 3(­x + 2) = x(x­2) – 3(x – 2) = (x – 2)(x – 3) Factor xy – 5y – 2x + 10. = xy – 5y – 2x + 10 What can factor out of the first pair? I can take out a " y": = y(x – 5) – 2x + 10 What can factor out of the second pair? Take out a "–2": = y(x – 5) – 2(x – 5) = (x – 5)(y – 2) A "quadratic" is a polynomial that looks like "ax2 + bx + c", where "a", "b", and "c" are just numbers. For the easy case of factoring, you will find two numbers that will not only multiply to equal the constant term "c", but also add up to equal "b", the coefficient on the x­term. For instance: Factor x2 + 5x + 6. Factoring Trinomials Factor x2 + 5x + 6. We need to find factors of 6 that add up to 5. Since 6 can be written as the product of 2 a...
View Full Document

Ask a homework question - tutors are online